2020
DOI: 10.1140/epja/s10050-020-00229-2
|View full text |Cite
|
Sign up to set email alerts
|

New studies and a short review of heavy neutron-rich transfer products

Abstract: We present new results on multi-nucleon transfer reactions in low-energy collisions of $$^{48}\hbox {Ca}+{}^{238}\hbox {U}$$ 48 Ca + 238 U measured at the velocity filter SHIP of GSI Helmholtz Centre, where we observed around 90 different nuclides from Tl to Am ($$Z=$$ Z = 81–95). We followed the idea to use uranium targets for the synthesis of neutron-rich MNT products, particularly in the region below lead, which was triggered by model calculations. The $$\gamma $$ γ , $$\alpha $$ α and spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 93 publications
(171 reference statements)
0
17
0
Order By: Relevance
“…Significant progress has been made in theoretical predictions of nuclear masses using microscopic-macroscopic models, density functional models, and machine learning techniques [267,268]. A better theoretical understanding of fission at the endpoint of the r-process path (A∼300) has shown that these processes affect rprocess nucleosynthesis [269,270]. Predictions of reaction rates for heavy nuclei rely on accurate optical potentials, and efforts are underway to calculate these from first principles [18,271].…”
Section: How Did We Get Here?mentioning
confidence: 99%
See 2 more Smart Citations
“…Significant progress has been made in theoretical predictions of nuclear masses using microscopic-macroscopic models, density functional models, and machine learning techniques [267,268]. A better theoretical understanding of fission at the endpoint of the r-process path (A∼300) has shown that these processes affect rprocess nucleosynthesis [269,270]. Predictions of reaction rates for heavy nuclei rely on accurate optical potentials, and efforts are underway to calculate these from first principles [18,271].…”
Section: How Did We Get Here?mentioning
confidence: 99%
“…Other facilities around the world, like FAIR in Europe, ISAC-ARIEL in Canada, and RIKEN/RIBF in Japan are also producing nuclei far from stability in complementary ways. A more niche but no less important path to heavy neutron-rich nuclides will be offered by multinucleon transfer reactions at JYFL and FAIR [326,269]. The experimental techniques and devices required to take advantage of the new beams have mostly been developed.…”
Section: What Needs To Be Done?mentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]) and by new experimental results (see e.g. [10,11,[55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, a new class of magnetic separators [10][11][12] with large acceptance, has been put to use in the study of MNT reactions [13][14][15]. Production of neutron-rich nuclides in damped collisions has been studied recently with novel applications of a few recoil separators which were not originally designed and built for this purpose [16][17][18]. Production of nuclei far from the stability region in multi-nucleon transfer reactions using a high resolution magnetic spectrometer has also been reported recently [19].…”
Section: Introductionmentioning
confidence: 99%